Usefulness of a new parameter in functional assessment in patients with idiopathic pulmonary fibrosis: desaturation - distance ratio from the six-minute walk test - Aktan, Rıdvan; Tertemiz, Kemal Can; Yiğit, Salih; Özalevli, Sevgi; Özgen Alpaydın, Aylin; Uçan, Eyüp Sabri (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: New parameters in the 6-minute walk test (6MWT) are needed for assessing exercise capacity in patients with idiopathic pulmonary fibrosis (IPF). To our knowledge, no previous study has investigated the potential of using the desaturation distance ratio (DDR) to assess exercise capacity specifically in patients with IPF. This study aimed to investigate whether DDR is a potential tool for assessing the exercise capacity of patients with IPF.Methods: This study conducted with 33 subjects with IPF. Pulmonary function tests and a 6MWT were performed. To calculate the DDR, first, the difference between the patient's SpO2 at each minute and the SpO2 of 100% was summed together to determine the desaturation area (DA). Next, DDR was calculated using dividing DA by the 6-minute walk test distance (6MWD) (i.e., DA/6MWD).Results: When correlations of 6MWD and DDR with changes (Δ) in the severity of perceived dyspnea were examined, 6MWD did not significantly correlate with ΔBorg. Conversely, there was a significant correlation between the DDR and ΔBorg (r= 0.488, p=0.004). There were significant correlations between 6MWD and FVC % (r=0.370, p=0.034), and FEV1 % (r=0.465, p=0.006). However, DDR was significantly more correlated with FVC % (r= -0.621, p< 0.001), FEV1 % (r= -0.648, p< 0.001). Moreover, there was a significant correlation between DDR and DLCO % (r= -0.342, p=0.052).Conclusions: The findings of this study suggest that DDR is a promising and more useful parameter for assessing patients with IPF.